2021
DOI: 10.1097/ccm.0000000000004967
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Serum Angiotensin II Levels in Prognosis of Patients With Coronavirus Disease 2019

Abstract: OBJECTIVES: We aimed to determine serum angiotensin II levels in patients with coronavirus disease 2019 infection and to investigate the effect of these levels on the prognosis of the disease. DESIGN: The study was planned prospectively and observationally. SETTING: The study was conducted in a tertiary university hospital. PATIENTS: Coronavirus disease 2019 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…This association is also observed in other critical care settings, such as distributive shock or cardiac surgery as a consequence of a relative deficit of angiotensin II, which induces renin release via a positive-feedback loop 129 , 130 . The existence of a similar mechanism in COVID-19 is suggested by the presence of lower angiotensin II levels in patients with COVID-19 and ARDS than in patients with milder disease 131 .…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 81%
“…This association is also observed in other critical care settings, such as distributive shock or cardiac surgery as a consequence of a relative deficit of angiotensin II, which induces renin release via a positive-feedback loop 129 , 130 . The existence of a similar mechanism in COVID-19 is suggested by the presence of lower angiotensin II levels in patients with COVID-19 and ARDS than in patients with milder disease 131 .…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 81%
“…The meta-analysis that we carried out in the previous section has shed some light on these questions to a certain extent, but many points remain obscure. Indeed, the experimental and clinical data that we collected from the literature about e.g., the levels of proteins and peptides involved in RAS and the activity of the enzymes, partially disagree [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…We review here recent data about measurements of RAS components in COVID-19. For that purpose, we manually collected and screened a series of clinical and experimental results from [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], listed in Supplementary Table S1. The individuals enrolled in these studies were classified into two or three classes: COVID-19 patients or severe and moderate COVID-19 patients, and controls or asymptomatic patients.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 99%
“…These observations suggest that severe COVID-19 is associated with global RAS dysregulation but not simply with a skewed balance in favor of ACE1 activity. This might reflect a global reduction of ACE1 and ACE2 expression in the damaged lung [103,104], a hypothesis which will deserve confirmation.…”
mentioning
confidence: 92%
“…The role of ACE1/ACE2 imbalance and ATII signaling in COVID-19 remains, however, to be clarified. Indeed, while early data indicated a positive correlation between circulating ATII levels and the severity of the disease [102], two recent studies reported contrasting results with lower circulating ATII in non-survivors [103,104]. These observations suggest that severe COVID-19 is associated with global RAS dysregulation but not simply with a skewed balance in favor of ACE1 activity.…”
mentioning
confidence: 98%